1936
DOI: 10.1017/s0022172400043618
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Incidence of Cancer of the Lung and Larynx

Abstract: XIIISummaryThe death certificates for cancer of the lung and of the larynx in males from England and Wales for the years 1921–32 inclusive, numbering 18,280, have been investigated.Sources of error in statistical work on death certificates are discussed.Latterly autopsies have been made upon about 28 per cent, of cases of cancer of the lung, and 9 per cent, of cases of cancer of the larynx. The increase in the recorded cases of lung cancer is not nearly accounted for by the increase of data obtained by autopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1939
1939
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…This causes respiratory tract tumors in the hamster and is relevant to human exposure, since atmosphere BP is also adsorbed to particulates. Epidemiological studies on health effects of PAH, though difficult to obtain because of widespread but low or varied exposure, have shown that gas production workers and coal tar pitch workers do have higher incidences of lung cancer in addition to skin and bladder cancers (14)(15)(16)(17)(18). Living in areas with high pollution increases lung cancer incidence (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…This causes respiratory tract tumors in the hamster and is relevant to human exposure, since atmosphere BP is also adsorbed to particulates. Epidemiological studies on health effects of PAH, though difficult to obtain because of widespread but low or varied exposure, have shown that gas production workers and coal tar pitch workers do have higher incidences of lung cancer in addition to skin and bladder cancers (14)(15)(16)(17)(18). Living in areas with high pollution increases lung cancer incidence (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…However, as a carcinogenic substance iron has attracted comparatively scant attention. Nevertheless Kennaway and Kennaway (1936) demonstrated that iron and steel grinders had 2.5 times as high an incidence of lung cancer as the population at large. Faulds (1954) found that lung cancer had a prevalence of 8.85 per cent (17 of 192) amongst iron mine workers.…”
mentioning
confidence: 99%
“…(1991) Assessment Kennaway and Kennaway (1947) analysed the mortality from cancer of the lung and larynx by occupation in England and Wales in 1921-38 that had been reported earlier (Kennaway & Kennaway, 1936). Data on occupation were obtained from death certificates; the population at risk in each occupation was estimated from national census data, which allowed the calculation of age-adjusted expected numbers of cancers by occupation.…”
Section: Regulations and Guidelinesmentioning
confidence: 99%